Unusually weak irradiation effects in anisotropic iron-based superconductor RbCa2Fe4As4F2 - Torsello, Daniele; Piatti, Erik; Fracasso, Michela; Gerbaldo, Roberto; Gozzelino, Laura; Yi, Xiaolei; Xing, Xiangzhuo; Shi, Zhixiang; Daghero, Dario; Ghigo, Gianluca (Frontiers in Physics, 2024)
We report on the effects of 3.5 MeV proton irradiation in RbCa 2 Fe 4 As 4 F 2 , an iron-based superconductor with unusual properties in between those of the pnictides and of the cuprate hightemperature superconductors. We studied how structural disorder introduced by ion bombardment affects the critical temperature, superfluid density and gap values by combining a coplanar waveguide resonator technique, electric transport measurements and point-contact Andreevreflection spectroscopy. We find an unusually weak dependence of the superconducting properties on the amount of disorder in this material when compared to other iron-based superconductors under comparable irradiation conditions. The nodal multigap state exhibited by pristine RbCa 2 Fe 4 As 4 F 2 is also robust against proton irradiation, with a two-band d-d model being the one that best fits the experimental data.